Experimental test results of an automatic voltage regulator with independent phase voltage controllers - Śleszyński, Wojciech; Cichowski, Artur; Szwarc, Krzysztof Jakub; Małkowski, Robert; Szczepankowski, Paweł; Augusiak, Andrzej; Karkosiński, Dariusz; Strzelecki, Ryszard (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The growing number of distributed renewable energy sources and dynamic constant-power loads (e.g. electric vehicle charging stations) pose new challenges for network operators. These changes result in alterations to network load profiles and load flows, leading to greater voltage volatility. One effective solution to these problems can be the use of automatic voltage regulators (AVRs), which stabilize and symmetrize voltage output, whether at distribution transformers (DTs) or elsewhere in the distribution network. The device developed by the authors consists of two bidirectional power converters and three single-phase transformers connected in series to the low-voltage grid as a stabilizer. The proposed control system provides accurate and fast regulation of the AVR output voltage (within the range of ±10% of the nominal grid voltage), with each phase being independently adjusted, regardless of the type of power load. The article includes test results demonstrating selected functionalities of the developed AVR. The physical model of the device discussed in the article is a research component of the LINTE2 laboratory of the Gdańsk University of Technology.